PTU-062 Vedolizumab: Early Experience and Medium-Term Follow up Data from Two UK Tertiary IBD Centres. (17th August 2016) - Samaan, MA; Pavlidis, P; Johnston, E; Warner, B; Digby-Bell, J; Koumoutsos, I; Fong, S; Goldberg, R; Gulati, S; Medcalf, L; Sastrillo, M; Bedwell, T; et al.
Abstract : Introduction: Vedolizumab was recently granted NICE approval for moderate-to-severe Crohn's disease (CD) and ulcerative colitis (UC). Novel pathways agreed by our CCG meant that patients at Guy's & St. Thomas' and King's College Hospitals had early access to vedolizumab. Methods: Records of patients commencing vedolizumab between Nov 2014–15 were screened. Those completing at least 14 weeks of treatment were included. Clinical activity was assessed using Harvey-Bradshaw Index (HBI) or Simple Clinical Colitis Activity Index (SCCAI) at baseline, 14 and 30 weeks. Response: HBI/SCCAI reduction ≥3. Remission: HBI < 5 or SCCAI <3. Continuous data are summarised as medians (range). Pre- and post-induction values were compared using Wilcoxon signed-rank test. Results: 60 patients (CD: 32, 53%, UC 25, 42%, IBD-U 3, 5%) commenced vedolizumab (m:f 29:31, age: 39 (18–74), follow-up: 5 months (1–13)). 19 were excluded from our analysis (3 IBD-U, 5 stomas, 11 treated for <14 weeks). Clinical data from the remaining 41 was analysed. Of 32 patients with active disease at baseline, 17 (53%) responded and 11 (34%) achieved remission by week 14. The response and remission rates for CD were 8/15 (53%) and 6/15 (40%). In UC they were 9/17 (53%) and 5/17 (29%). Response and remission rates in anti-TNF experienced patients were 12/26 (46%) and 6/36 (35%) compared to 5/6 (83%) and 5/6 (83%) in anti-TNF naïve patients, respectively. 7/11 (64%) with active disease at baseline who completed 30 weeks of treatment responded and achieved remission. Faecal calprotectin fell significantly (pre-induction: 1076 (90–4800), post-induction: 478 (10–3184), p = 0.029 for n = 14) and CRP remained stable (pre-induction: 4 (1–70), post-induction: 4 (1–72), p = 0.28 for n = 40). Rates of steroid use at each time point: 19/41 (46%) at baseline, 11/41 (21%) at week 14 and 3/15 (20%) at week 30. Surgery was required in 4/41 (10%, CD:3 and UC:1). Conclusion: Our experience mirrors a previously reported real-world cohort 1 and demonstrates similar efficacy to the GEMINI trials. This data demonstrates a meaningful reduction in clinical and biochemical disease activity as well as a steroid-sparing effect in patients with complex and previously refractory disease. We did not see a significant difference in efficacy between patients with UC and CD. Reference: 1 Christensen B. et al . Post-marketing experience of vedolizumab for IBD: The University of Chicago experience . ECCO; Barcelona, 2015. Disclosure of Interest: None Declared